Features of the combined course of opisthorchosis and lambliosis - T. E. Pomytkina; O. I. Bibik; O. I. Pivovar (Российский паразитологический журнал)
The purpose of the research is identifying and determining clinical and laboratory features of coinfection caused by Opisthorchis felineus and Lamblia intestinalis.Materials and methods. We described a clinical picture and laboratory abnormalities in 50 patients with O. felineus infection. Of these cases, 25 people were diagnosed with lambliosis. The therapy included three consecutive stages: preparatory stage, antiprotozoal and anthelmintic treatments, and rehabilitation stage. The preparatory stage was aimed to improve the biliary tract function, to reduce intoxication symptoms, and to stop acute allergic reactions. The patients received choleretics, antispasmodics, antibacterial drugs, antihistamines, enzymes, and adsorbents for 2–4 weeks. At the end of the preparatory stage, the patients from the second group were prescribed albendazole of 800 mg per day in two doses of 400 mg per os during meals for 5 days. In the second treatment stage, the patients with opisthorchosis received praziquantel at a dose of 75 mg/kg of body weight per os for one day in three doses. The rehabilitation phase lasted for four months. The next step was to assess lamblia eradication results by the control coproprotozooscopy and/or biliprotozooscopy for cysts and/or vegetative forms of L. intestinalis at 7 days, 1 month and 6 months after treatment with albendazole. The control coproovoscopy for O. felineus eggs was performed at 6 months after praziquantel treatment.Results and discussion. We studied the inﬂuence of L. intestinalis on the nature and severity of clinical and laboratory symptoms of opisthorchosis. It was revealed that clinical symptoms (abdominal pain, nausea, low-grade fever or dermatosis) and laboratory syndromes (cytolysis and cholestasis) were more pronounced in case of concomitant helminth and protozoan infections. Lambliosis is more difcult to treat when combined with opisthorchosis.